Analysis of the Productive Dimension of the Reintegration Process in Colombia - Álvarez-Ríos, Jorge Norvey; Gallego-González, Jaime Eduardo; Medrano-Benavides, José Luis; Abendaño-Beltrán, Camilo Andrés (Sociedad y Economía, 2022)
Colombia has opted for a reintegration process that seeks a stable and lasting peace. For this reason, it has created a public policy that includes different components. Among them, the productive dimension. The objective of this article is to describe the contribution of the productive dimension to the reintegration process of ex-combatants according to secondary sources. For this purpose, a systematic review was carried out, including scientific articles and public documentation derived from the reintegration process. The productive dimension is also analyzed from the point of view of the opportunities of the economic context, the responsibility of the private sector, labor linkage, and productive environment models. The dynamics of the reintegration process oriented to the productive and economic dimension contribute to peace building through the generation of employment opportunities, business strengthening, and the generation of sustainable income by ex-combatants.